Facilitated photocatalytic H2 production on Cu-coordinated mesoporous g-C3N4 nanotubes. Issue 7 (24th March 2023) - Su, Zhuizhui; Zhang, Jianling; Tan, Zhonghao; Hu, Jingyang; Zhang, Fengtao; Duan, Ran; Yao, Lei; Han, Buxing; Zhao, Yingzhe; Yang, Yisen
Abstract : Single-atom Cu-coordinated mesoporous g-C3 N4 nanotubes show excellent photocatalytic H2 production. Theoretical and experimental results show that Cu–N2 sites promote charge transfer and separation, and reduce the energy barrier of H2 production. Abstract : Photocatalytic conversion of solar energy to hydrogen (H2 ) provides an efficient way for energy supply and storage. It is of great importance to improve the H2 production efficiency by constructing photocatalysts with rapid charge transfer and separation and a low energy barrier for H2 production. Here, we demonstrate high-efficiency photocatalytic H2 production on Cu-coordinated mesoporous g-C3 N4 nanotubes. The catalyst exhibits a photocatalytic H2 production rate of 6.53 mmol g −1 h −1 under visible-light irradiation ( λ > 420 nm), which is much higher than that over bulk g-C3 N4 (0.58 mmol g −1 h −1 ) under the same conditions. Advanced characterization and density functional theory calculations reveal that such a catalyst has stronger light absorption, facilitated carrier transfer and separation, and a reduced H2 evolution barrier than Cu-free g-C3 N4 nanotubes. This study provides a new insight into the design of photocatalytically active sites of catalysts for high-performance H2 production.